MANAJEMEN PROGRAM PENDIDIKAN KESETARAAN KEJAR PAKET C DI PKBM SARIJAYA KECAMATAN TELUKJAMBE BARAT KABUPATEN KARAWANG - Syifa Retno Gumilang; Dayat Hidayat; Dadang Danugiri (IKIP Siliwangi, 2022)
This research aims to describe the process of planning, implementing and evaluating the management of equality education learning programs pursued by PKBM Sarijaya Telukjambe Barat, Karawang. In the management of this pake c chase education program behind various activity programs to fulfill the wishes of the community, it can be understood that PKBM is a means of education that can help the community. This research uses qualitative methods by taking a phenomenological approach intended to give a clear picture of the problems studied based on the experience experienced by informants. The subjects of this study are the Head of PKBM Sarijaaya, pamong or tutor, administrative staff and learning citizens. Data collection techniques using Observation, Interview and Documentation Techniques. Data analysis is done by identifying the collected data and then synthesized and compiled. The results of this study show that: (1) Program planning based on community learning needs, 2) Implementation of managed programs such as formal education coupled with the practice of life skills education, 3) Program evaluation includes formative evaluation, summative and final evaluation.